Frequency of Inactivated COVID-19 Vaccine Side Effects in a Tertiary Care Hospital of Karachi - Niazi, Ghulam Abbas Khan; Ishtiaq, Qasim; Khan, Jamal Azfar; Ather, Nadia Aziz; Satti, Muhammad Luqman (Pakistan Armed Forces Medical Journal, 2022)
Objective: to determine the frequency of the possible side effects of the COVID -19 inactivated vaccine. Study Design: Cross-sectional survey. Place and Duration of Study: Pakistan Naval Ship Shifa Hospital, Karachi Pakistan from Jan to Apr 2021. Methodology: A total of 305 recipients of inactivated COVID-19 vaccine were asked to fill out a questionnaire themselves or by the health care worker via telephonic conversation. The questionnaire comprised queries regarding general and local side effects that the participants experienced after getting vaccinated for COVID-19. Results: Out of 305 recipients, 270(88.5%) were men, and 35(11.5%) were women. Participants’ age ranged from 18-60 years.After the first dose, 83(27.2%) cases [male 63(23.3%) vs. female 20(57.1%)], were reported with side effects, while 75(24.5%)recipients, [male: 54(19.9%) vs. female: 21(58.8%)], had side effects after the second dose. Generalized symptoms were fever,headache, dizziness, and body aches, while local side effects were pain, itching, swelling and rash at the injection site.259(84.9%) recipients reported spontaneous recovery after the first dose. After the second dose, 286(93.8%) recipients recovered spontaneously. The remaining 44(13%) of the recipients’ required symptomatic treatment. After the second dose,only 19(6%) recipients needed symptomatic treatment. Conclusion: It is important to document the possible side effects of COVID vaccine so that public awareness and education can be made to minimize public fear of vaccine side effects. Inactivated vaccine for COVID-19 has minimal reported side effects and hence has a good safety profile.